O Papel do estado nos conflitos fundiários em razão do açaizal de várzea - PINHEIRO, Rodolfo Gonçalves (2022)
The State has a primary role in resolving land conflicts in the floodplain, drawn between traditional riverside communities and local hegemony. This situation is observed from the analysis of cases in 16 cases brought that together demonstrate the weakening of state institutions in the defense of the rights of traditional riverside populations. While figures who hold the political and economic power of the region use the absence of the state to disturb and / or drain, enslave and appropriate traditionally occupied public lands.